Direito e branquitude - Victor Schittini Teixeira (2021)
The main objective of this bibliographic research is to problematize Brazilian whiteness in the Law field, considering it as a behavioral and argumentation framework that, when shared, characterizes the racial identity of white Brazilians. Thus, the main focus is to understand how this racial group identity manifests in a legal phenomenon. Firstly, with the purpose of demonstrating how critical studies of whiteness can contribute to the promotion of an emancipatory and decolonial legality, this work is introduced by problematizing the hegemonic legal paradigm of Western modernity from a Latin-American decolonial turn point of view. A historical and sociological study of the racial thinking evolution in the Eurocentric modernity is developed, evidencing how the concept of race becomes structured by the modern Western thinking to categorize, describe, and especially rank human groups based on their physical and cultural traits. The development of racial thinking by Brazilian intellectuals from the 20th century onwards is brought into focus, demonstrating how most racial studies in the country overlook whiteness position as an active part in the reproduction of structural racism of Brazilian society. After reflecting on racial thinking itself, this research addresses critical studies of the national whiteness and the thesis about the Brazilian racial humanism that, so to speak, promote a shift in the focus of analysis of racial thinking and evidence the actions of whiteness in the reproduction of hegemonic and dominant paradigms of Western modernity and, consequently, in the reproduction of Brazilian society’s structural racism. Lastly, the arguments disseminated by the political party Partido Democratas in the initial pleading of ADPF [action against the violation of a constitutional fundamental right] no. 186 are analyzed in order to evidence how the technical rhetoric of Brazilian whiteness and racial humanism manifests in the Law field.